Voting for mobile citizens - Matthias Wrede (Philipps-University Marburg, Faculty of Business Administration and Economics, 2008)
This paper analyzes inter- and intraregional redistribution in a centralized state using the citizen-candidate model. It focuses on conflicting interests among regions and among citizens of varying mobility. If discrimination with respect to place of residence and degree of mobility is possible, diversity of interests is high. Under the plurality rule and with sincere voting, the largest socioeconomic group of citizens supplies the winning candidate and discriminates against all other groups. However, if discrimination with respect to the degree of mobility is constrained, mobile citizens may gain power and interregional redistribution is reduced.
Keywords: D7; H1; H7; 330; Voting; mobility; inter- and intraregional redistribution; discrimination